2013
DOI: 10.1074/jbc.m113.474452
|View full text |Cite
|
Sign up to set email alerts
|

Ligands Raise the Constraint That Limits Constitutive Activation in G Protein-coupled Opioid Receptors

Abstract: Background: Native subtypes of G protein-coupled receptors (GPCR) show different levels of constitutive activation. Results: Using a BRET assay to detect receptor-G protein complexes, we find that constitutive activation causes a uniform reduction of the apparent efficacy of all ligands. Conclusion: An intramolecular energy barrier separates constitutive from ligand-regulated activation. Significance: The data suggest that GPCR activation involves both cooperative and anticooperative components.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
22
2

Year Published

2014
2014
2019
2019

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 20 publications
(25 citation statements)
references
References 34 publications
1
22
2
Order By: Relevance
“…Very recently using a BRET-based assay to investigate NOP receptor/G-protein interactions, it was demonstrated that GDP was not able to significantly inhibit the baseline BRET ratio (Malfacini et al, 2015). However, in membranes expressing the other opioid receptors, under similar experimental conditions, GDP can suppress the baseline BRET ratio, indicating a reduction in spontaneous receptor/G-protein interactions, with maximal effects 4-5 times greater at delta than mu receptors (Vezzi et al, 2013). Thus these results demonstrate that the propensity to display constitutive activity is much lower for NOP compared with the mu and particularly the delta opioid receptor.…”
Section: A Nociceptin Opioid Peptide Receptor Proteinmentioning
confidence: 99%
“…Very recently using a BRET-based assay to investigate NOP receptor/G-protein interactions, it was demonstrated that GDP was not able to significantly inhibit the baseline BRET ratio (Malfacini et al, 2015). However, in membranes expressing the other opioid receptors, under similar experimental conditions, GDP can suppress the baseline BRET ratio, indicating a reduction in spontaneous receptor/G-protein interactions, with maximal effects 4-5 times greater at delta than mu receptors (Vezzi et al, 2013). Thus these results demonstrate that the propensity to display constitutive activity is much lower for NOP compared with the mu and particularly the delta opioid receptor.…”
Section: A Nociceptin Opioid Peptide Receptor Proteinmentioning
confidence: 99%
“…On the other hand, cellular mechanisms may warrant high concentrations of signaling partners in physiologic conditions and, at the same time, mass action is most likely only one of many factors influencing DOPr association into multimeric arrays. For example, although the spontaneous transfer of energy between BRET pairs consisting of DOPr and Gb1 subunits was susceptible to modulation by guanine nucleotides, the interaction between overexpressed MOPrs and Gb1 was not (Molinari et al, 2010), arguing that high constitutive activity and not only mass action may have contributed to the spontaneous association between DOPr and G proteins (Costa and Herz, 1989;Vezzi et al, 2013).…”
Section: D-opioid Receptor Pharmacologymentioning
confidence: 99%
“…Second, the increase in constitutively active MORs could be a result of a change in the intrinsic energy constraint that limits constitutive activity (Vezzi et al, 2013). This new model is an extension to the extended ternary complex model (De Léan et al, 1980;Wreggett and De Léan, 1984;Weiss et al, 1996) and proposes that an intrinsic, intramolecular energy constraint limits constitutive activity.…”
Section: Mechanisms For Mor Constitutive Activitymentioning
confidence: 99%